Essays on Multinational Production and International Trade - Federico Clementi (Copenhagen Business School (CBS), 2017)
This Thesis consists of an introduction followed by three independent chapters. Each chapter is a self-contained paper that can be read independently. They cover different topics of international economics with a specific focus on multinational production and international trade. A common feature to all the papers is that they are micro-based empirical analyses of the effects of globalization on the competitiveness of companies. The first and last chapters are solo papers, while the second is coauthored with Friedrich Bermann, PhD student at Copenhagen Business School. The first paper studies the impact of foreign direct investment on the intensity of competition in the host economy. In this chapter I use firm-level data of Romanian manufacturing companies active between 2001 and 2008 and I measure the impact of foreign ownership on the market power of affiliates and local competitors. The empirical evidence shows that foreign ownership is associated to a higher market power, which I proxy with firms' estimated markups. Moreover, I find that higher competition of foreign affiliates is associated to a decrease in the markups charged by domestic firms. In the second chapter we analyze how the strategy of vertical integration of foreign multinationals modifies the nature of productivity spillovers perceived by local suppliers (i.e. backward spillovers). Building on the results of previous research on productivity spillovers and on multinational production, we argue that backward productivity spillovers should be weaker if foreign multinationals are vertically integrated in the industry of local suppliers. We test this hypothesis using a panel dataset of firm-level data of European manufacturing companies. We find that the vertical integration of foreign multinationals does in fact modify the intensity of spillovers to local suppliers. Domestic firms benefit only from the activity of foreign clients that are not vertically integrated in their industry. In the last chapter, I use a detailed dataset of international transactions of Danish companies to study the impact of Chinese competition on the pricing strategy of Danish exporters. I also explore the role of quality differentiation in determining the nature and intensity of this effect. I find that Chinese export represents a source of stiffer competitive pressure for Danish exporters that are forced to reduce the prices they charge. This effect depends on the quality of Danish products. I find the producers of low-quality goods reduce their prices less intensively than producers of high-quality ones. This is because producers of low-quality varieties react to Chinese competition upgrading the quality of their products. This mitigates the downward pressure on prices. I finally reconcile these results by using quality-adjusted prices. Using this measure I find that quality does in fact protect Danish exporters from the pressure of Chinese competition.
hdl:10398/9469
Keywords: 650